Arrhythmia monitoring and outcome after myocardial infarction (BIO|GUARD-MI): a randomized trial - Jøns, Christian; Bloch Thomsen, Poul Erik; Riahi, Sam; Smilde, Tom; Bach, Ulrich; Jacobsen, Peter Karl; Táborský, Miloš; Faluközy, Jozsef; Wiemer, Marcus; Christensen, Per Dahl; Kónyi, Attila; Schelfaut, Dan; et al. (Frontiers in Cardiovascular Medicine, 2024)
Objectives Cardiac arrhythmias predict poor outcome after myocardial infarction (MI). We studied if arrhythmia monitoring with an insertable cardiac monitor (ICM) can improve treatment and outcome. Design BIO|GUARD-MI was a randomized, international open-label study with blinded outcome assessment. Setting Tertiary care facilities monitored the arrhythmias, while the follow-up remained with primary care physicians. Participants Patients after ST-elevation (STEMI) or non-ST-elevation MI with an ejection fraction >35% and a CHA2DS2-VASc score ≥4 (men) or ≥5 (women). Interventions Patients were randomly assigned to receive or not receive an ICM in addition to standard post-MI treatment. Device-detected arrhythmias triggered immediate guideline recommended therapy changes via remote monitoring. Main outcome measures MACE, defined as a composite of cardiovascular death or acute unscheduled hospitalization for cardiovascular causes. Results 790 patients (mean age 71 years, 72% male, 51% non-STEMI) of planned 1,400 pts were enrolled and followed for a median of 31.6 months. At 2 years, 39.4% of the device group and 6.7% of the control group had their therapy adapted for an arrhythmia [hazard ratio (HR) = 5.9, P < 0.0001]. Most frequent arrhythmias were atrial fibrillation, pauses and bradycardia. The use of an ICM did not improve outcome in the entire cohort (HR = 0.84, 95%-CI: 0.65–1.10; P = 0.21). In secondary analysis, a statistically significant interaction of the type of infarction suggests a benefit in the pre-specified non-STEMI subgroup. Risk factor analysis indicates that this may be connected to the higher incidence of MACE in patients with non-STEMI. Conclusions The burden of asymptomatic but actionable arrhythmias is large in post-infarction patients. However, arrhythmia monitoring with an ICM did not improve outcome in the entire cohort. Post-hoc analysis suggests that it may be beneficial in non-STEMI patients or other high-risk subgroups. Clinical Trial Registration [https://www.clinicaltrials.gov/ct2/show/NCT02341534], NCT02341534.